Penerapan User Centered Design dalam Pembangunan Aplikasi Informasi Hostel berbasis Android - Diah Shinta Dewi; Adam Hendra Brata; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The current technological developments, especially on mobile devices are very helpful to human activities. Travelers have problem of limited access to detail information about the location of hostel. Data from the Department of Culture and Tourism of Malang said, the surge of tourists who data on the city is quite significant. The impact is the growing business of hostels in the city. The cheap price and the complete facilities are the factors that make many travellers choose a hostel as a place to stay. However, there is no special container to accommodate the lodging's complete information. By looking at these conditions, the application of a special hostel information system in Malang was developed. This application is implemented on Android smartphones by using User Centered Design method that refers to the User Experience of potential users. The main purpose of the method is to create a user-friendly information system with a high usability level.Based on three usability testing criteria are effectiveness, efficiency and user satisfaction level. Then the resulting value on usability testing according to effectiveness is 91.7%, according to efficiency is 100%, and according to user satisfaction of 84.5%. From these three results can be calculated average usability rate of 92.06%. So, it can be concluded that this application has a high level of usability and become a user-friendly application.